Poikiloderma vasculare atrophicans: A distinct clinical entity? - Vikram K Mahajan; Pushpinder S Chauhan; Karaninder S Mehta; Anju Lath Sharma (Wolters Kluwer Medknow Publications, 2015)
This paper describes a typical case of poikiloderma vasculare atrophicans (PVA) in a 48-year-old female. Histologically, the features were suggestive of PVA with the absence of Pautrier's microabscess or atypical lymphoid cells. The biopsy specimen was positive for cluster of differentiation (CD) 8 on immunohistochemical staining. Its exact pathogenesis remains obscure, and it remains unclear whether PVA actually is mycosis fungoides (MF), a forme fruste of MF, or a distinct and benign dermatosis with CD8+ phenotype that can perhaps be labeled as PVA. However, it has a long benign clinical course without progression to tumor stage of MF in most cases, and its status within the spectrum of cutaneous T-cell lymphoma remains poorly understood. Yet it is imperative to distinguish PVA from poikilodermic MF.